"We must assess all, even a student farting [is also assessed] for the behavioural aspect of learning": Teachers' conceptions of assessment in the context of assessment reform in Indonesia. Issue 1 (6th September 2021) - Arrafii, Mohammad Arsyad
Abstract: This paper explores Indonesian secondary school teachers' conceptions of assessment in the context of assessment reform. Teachers working at different school level were interviewed both individually and in groups and their responses were analysed using the content analysis approach. Detailed examination of teachers' assessment propositions revealed that their perspectives about assessment embrace values, purposes, and understanding, and are marked by conceptions about the learner agency, accountability and improvement orientations. However, despite being considered important, the learner agency and accountability conceptions were often considered irrelevant. In addition, teachers reported tension with regard to their perceptions towards the reform and demonstrated a varied level of conceptual and practical understanding of the reform. The paper ends with a discussion of the complex nature of and tensions in the teachers' conceptions of assessment. Principal implications are discussed.